HOW GAMES CAN INSPIRE LEARNING - Kamila Turaboyeva (Лучшие интеллектуальные исследования, 2023)
Annotation: Game-based learning is an umbrella term that can describe many different ways to use games as a tool for education. Learning and teaching with games is nothing new, teachers have been using physical games, board games and card games in a range of subjects for years as a strategy to motivate students and make learning more approachable. Digital technologies, including virtual and augmented reality, allow teachers to bring even more engaging learning experiences into the classroom.